Introducing Early Coding: A Simple Robotics Workshop for Early Childhood Teacher to Enhance Children’s Creativity - Muqodas, Idat; Fitri Maryana, Anitia; Nur Anggraeni, Cintya; Marta Runaya, Kharisma; Maulidinda Akhmad Syam, Rahma; Lisnawati, Lisnawati (Journal of Islamic Education Students (JIES), 2025)
The need to strengthen digital literacy in early childhood education requires teachers to have an adequate understanding of practical coding learning. However, limited competencies and facilities remain an obstacle in many schools. This workshop program aims to improve the knowledge and skills of teachers at Melati Purwakarta Kindergarten through an introduction to simple robotics based on Scribble Bot. The research used a qualitative descriptive method through the stages of material delivery, mentoring, and direct practice. Data was collected through observation, interviews, and documentation, then analyzed using thematic analysis through the processes of coding, categorization, and theme extraction. The findings show that: (1) all participants were able to assemble the Scribble Bot independently, indicating an improvement in technical skills; (2) pedagogical understanding of the role of coding in children's cognitive, motor, and social development increased significantly; and (3) a commitment to sustainable implementation emerged in the form of plans to integrate simple robotics into monthly learning. This program has implications for increasing teachers' readiness to adopt more innovative coding learning and emphasizes the need for facility support and further training so that the integration of robotics in early childhood education can be sustainable.